Economic Issues with Value-Enhanced Corn - Boland, Michael; Domine, Matthew; Dhuyvetter, Kevin C.; Herrman, Tim J. (My University, 1999)
This publication provides an overview of valule-enhanced corn in Kansas.
MF2430_1999_11
Keywords: MF2430; Economics; Crops; MF